1979
DOI: 10.1159/000137258
|View full text |Cite
|
Sign up to set email alerts
|

Modification of D-Galactosamine-Induced Liver Injury in the Rat by Spironolactone

Abstract: Spironolactone, a competitive inhibitor of mineralocorticoid effects on the distal tubule of the kidney, has recently been found to have other metabolic effects. In these studies, spironolactone (200 mg/kg intraperitoneally) for 3 days was found to have a marked protective effect against the hepatotoxic effect of D-galactosamine (275 mg/kg) in rats. Further progress in defining the mechanism of protection from D-galactosamine hepatic necrosis by spironolactone will require assessment of effects of spironolacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
0
1
Order By: Relevance
“…In rat models, spironolactone decreased ALT and liver toxicity induced by dimethyl mercury 36 or D-galactosamine. 37 In this study, HOMA-IR was significantly decreased within group 2, whereas QUICKI showed a trend towards increase (meaning IR improvement) in the same group without reaching the level of statistical significance. This is not unexpected, since it has been previously reported that both HOMA and QUICKI reflect insulin action expressed by clamps, 16,17 but they do not offer the same information about IR, thereby expressing different aspects of insulin action.…”
Section: Discussioncontrasting
confidence: 46%
“…In rat models, spironolactone decreased ALT and liver toxicity induced by dimethyl mercury 36 or D-galactosamine. 37 In this study, HOMA-IR was significantly decreased within group 2, whereas QUICKI showed a trend towards increase (meaning IR improvement) in the same group without reaching the level of statistical significance. This is not unexpected, since it has been previously reported that both HOMA and QUICKI reflect insulin action expressed by clamps, 16,17 but they do not offer the same information about IR, thereby expressing different aspects of insulin action.…”
Section: Discussioncontrasting
confidence: 46%